Advances in mergers and acquisitions. - Finkelstein, Sydney; Cooper, Cary L. (Advances in mergers and acquisitions ;, 2016)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspectives. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The papers published in this volume provide cutting edge ideas by leading scholars, and help to inform mergers and acquisitions research around the world.